Association between the Glu298Asp and T(-786)C polymorphisms of the endothelial nitric oxide synthase gene and respiratory distress in preterm neonates - Sivasli, Ercan; Babaoğlu, Melih; Yaşar, Umit; Yurdakök, Murat; Bozkurt, Atila; Korkmaz, Ayşe; Yiğit, Sule; Tekinalp, Gülsevin (The Turkish Journal of Pediatrics, 2010)
Genetic polymorphisms in the gene that codes for endothelial nitric oxide synthase (eNOS) have been associated with less nitric oxide availability and with various cardiovascular diseases in humans. The objective of this study was to analyze the genotype distributions and allele frequencies for the Glu298Asp (G894T) and T(-786)C polymorphisms of the eNOS gene among neonates with respiratory distress in comparison to healthy control subjects. Fifty premature neonates with respiratory distress and 55 neonates without any respiratory problem were included in the study. Genomic DNA from all the neonates was analyzed by polymerase chain reaction. A polymerase chain reaction-restriction fragment length polymorphism analysis of eNOS gene polymorphisms was performed, and the results were compared. There were no significant differences between the groups regarding either genotype distributions or the allele frequencies for the Glu298Asp and T(-786)C polymorphisms. These results suggest that eNOS Glu298Asp and T(-786)C polymorphisms are not associated with development of respiratory distress.